2013
DOI: 10.1002/bjs.9192
|View full text |Cite
|
Sign up to set email alerts
|

Consensus statement on the multidisciplinary management of patients with recurrent and primary rectal cancer beyond total mesorectal excision planes

Abstract: Consensus abstractBackground: The management of primary rectal cancer beyond total mesorectal excision planes (PRCbTME) and recurrent rectal cancer (RRC) is challenging. There is global variation in standards and no guidelines exist. To achieve cure most patients require extended, multivisceral, exenterative surgery, beyond conventional total mesorectal excision planes. The aim of the Beyond TME Group was to achieve consensus on the definitions and principles of management, and to identify areas of research pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(47 citation statements)
references
References 17 publications
0
46
0
1
Order By: Relevance
“…These procedures are technically challenging and their roles are still debatable. Two recent Delphi studies[60,61], have confirmed the views of many world experts that extensive lateral side wall involvement still remains a relative contraindication to curative surgery.…”
Section: Surgical Approach Based On Location Of Diseasementioning
confidence: 74%
“…These procedures are technically challenging and their roles are still debatable. Two recent Delphi studies[60,61], have confirmed the views of many world experts that extensive lateral side wall involvement still remains a relative contraindication to curative surgery.…”
Section: Surgical Approach Based On Location Of Diseasementioning
confidence: 74%
“…This is a non-interventional study, no supplementary examinations to those performed in the framework of patient care management will be carried out for the inclusion of patients. According to the guidelines established by a consensus of international experts [ 1 ], before inclusion, the patients should have a pelvic MRI and a thoracoabdominal-pelvic scan. Patients should be included after MDT meeting discussion, irrespective of a curative or palliative treatment decision.…”
Section: Methods and Designmentioning
confidence: 99%
“…These anatomical limits can affect the resectability of primary rectal cancer beyond the total mesorectal plane (PRC-bTME) and locally recurrent rectal cancer (LRRC). In fact, 5 to 10 % of cases of rectal cancer are bTME at the time of diagnosis with an extension to an adjacent organ (T4bNxM0) limiting their resectability [ 1 , 2 ]. After radiochemotherapy, 30 % of these tumours will be resectable at the cost of extensive pelvic surgery and 10 % remain non-resectable [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, curative excision is possible in fewer than half of patients with recurrent rectal cancer [6-8]. Radiotherapy or chemoradiotherapy are the alternative treatments for unresectable recurrent cases [9]. Various symptoms are reported in 71%–89% of patients with locally recurrent rectal cancer [8,10].…”
Section: Introductionmentioning
confidence: 99%